2012
DOI: 10.1080/00150193.2012.684598
|View full text |Cite
|
Sign up to set email alerts
|

Blue Phase III—Isotropic Phase Transition in a Bent-Core Liquid Crystal with Chiral Dopant

Abstract: Calorimetric measurements and optical observations have been performed to investigate the effect of chirality on a bent-core nematic (BCN) material which can exhibit an amorphous blue phase (BPIII) over a wide temperature range by mixing with a highly chiral dopant. It was found that the first-order character of the nematic (N)-isotropic (I) phase transition of the host BCN sample was clearly weakened by increasing the chiral dopant concentration and eventually moved into the supercritical evolution. The color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[32] As shown in Figure 4, it is likely that the dielectric anisotropies of T4 and M12 are essentially the same.O nt he other hand, our preliminary study by high-resolution calorimetric measurements showedt hat the BP mixture formed by M12 + BDH1281 3.9 wt %w as in as upercritical state, i.e.,a nu ltimately short pitch regime of BPIII. [33] Consequently,t he difference in P seems to be more plausible. B depends on the square of P,a nd thus stronger than other parameters as showni n[ Eq.…”
mentioning
confidence: 99%
“…[32] As shown in Figure 4, it is likely that the dielectric anisotropies of T4 and M12 are essentially the same.O nt he other hand, our preliminary study by high-resolution calorimetric measurements showedt hat the BP mixture formed by M12 + BDH1281 3.9 wt %w as in as upercritical state, i.e.,a nu ltimately short pitch regime of BPIII. [33] Consequently,t he difference in P seems to be more plausible. B depends on the square of P,a nd thus stronger than other parameters as showni n[ Eq.…”
mentioning
confidence: 99%
“…12 The highresolution calorimetric measurement revealed that with the increasing wt % of the chiral dopant, the first-order characteristic of the nematic (N)�isotropic (I) transition of the host bentcore nematic (BCN) was weakened, and there is a blue shift of the texture. 13 The idea of designing the host LCs for the thermal stability of BPs is discussed and found that the smaller value of dielectric anisotropy (Δε) and the higher value of the elastic constant are desired for the purpose. 14 To optimize the device's performance, a detailed study has been made on the Kerr effect and re-established the quadratic relation between operating voltage (V on ) and K, that is, V K on 1 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…There is an excellent review article by Rahman et al where they discussed the strategies for phase stabilization and device development from BPs by considering the different possibilities such as the incorporation of nanoparticles (NPs), mixing with polymers, designing different types of electrodes, and so forth . The high-resolution calorimetric measurement revealed that with the increasing wt % of the chiral dopant, the first-order characteristic of the nematic (N)isotropic (I) transition of the host bent-core nematic (BCN) was weakened, and there is a blue shift of the texture . The idea of designing the host LCs for the thermal stability of BPs is discussed and found that the smaller value of dielectric anisotropy (Δε) and the higher value of the elastic constant are desired for the purpose .…”
Section: Introductionmentioning
confidence: 99%